123I intercomparison exercises: Assessment of measurement capabilities in UK hospitals. (April 2018) - Ferreira, Kelley M.; Fenwick, Andrew J.
Abstract: Three comparison exercises have been performed in 1996, 1999 and 2015 with 123 I to assess the UK hospitals measurement capabilities using radionuclide calibrators for this particular radionuclide. The exercise performed in 1996 showed that only 62% of the participants could measure the solution to within 10% of the standardised value and only 28% could measure within 5% of the certificated value. The intercomparison exercise performed in 1999 showed no improvement in the measurement capability, with only 66% of the participants measuring to within 10% of the standardised value. The exercise performed in 2015 showed great improvement in the hospitals measurement capability, 94% of participants reported results within 10% of the certificated activity and 85% of the participants reported results within the 5% of the reported activity. The intercomparison exercises are an important way to identify possible measurement problems within the medical community. Additionally, the intercomparison exercises provide hospitals with traceability to national primary standards and improve measurement capability within the Nuclear Medicine community. Highlights: 123 I intercomparison exercise. Assessment of measurement capability in the UK using Radionuclide calibrators. 28% of the reported results reported in 1996 are within 5%. 85% of the reported results reported in 2015 are within 5%. Continued training is essential to improve measurement capability.